The Establishment of Gwǝlt and Rim Landholdings in Eighteenth-Century Gondärine Churches with a Special Focus on Ḥamärä Noḫ Śälästu Mǝʾǝt Däbr - Guebreyesus, Namouna; Abdu, Hiruy (Aethiopica, 2018)
The Ethiopian kings of the seventeenth and eighteenth centuries established churches endowed with large estates. The gwǝlt charter founding these estates conferred tax and jurisdictional privileges on the beneficiaries for the administration of the churches. On the land given as gwǝlt , individual holdings known as rim were distributed to clerics. The study defines the economic and social contexts in which the foundation of both gwǝlt and rim occurred and shows that such grants were a manifestation of the king’s prerogatives and that the creation of ecclesiastical holdings disturbed existing social status and entitlements to land. In a comprehensive analysis the study considers land documents from Gondärine churches, with an emphasis on the Golden Gospel of the church of Ḥamärä Noḫ. The commentaries of the Fǝtḥa nägäśt, composed in the same period as the Gondärine land documents, will serve to explain the legal framework of gwǝlt and rim as applied in the eighteenth century in regards to customary Gondärine practices. This study of gwǝlt and rim reveals landholding practises whereby several rights coexisted on the same land, a fundamental aspect of Ethiopian land tenure which continued until the Revolution of 1974.